The Relevance of Digital Infographics in Online Newspapers - Pinto, Julio Costa (European Scientific Journal, ESJ, 2017)
In the more developed societies online newspapers have already reached a very high degree of notoriety. The newspaper, besides being a product of the journalistic domain, is also the product of the visual domain. Due to the incorporation of new technologies and of different visual trends, substantial changes in consolidated models of newspaper design have been seen that originated a growth in the importance of the image that the newspaper has in the web. It was from this context that emerged the research described in this article. An analysis of the technique used in a specific aspect of the essential graphics in this model of communication: infographics, was carried out. To that purpose, a study of infographics in web journalism was performed, in order to determine its essencial elements.